Design of Quarter Car Test Bench to Measure Forces on the Tire Contact Path - B Bukhari (Malikussaleh University, 2017)
Suspension system that located between vehicle body and wheels are designed to absorb shock from road surface. The dynamic behavior of the suspension and tire is depends on many factors. Some of the main factors are the vehicle load, speed, steering angle and the magnitude of the elasticity of the tire. The position of the tire-road contact is also always changed when the vehicle running make it difficult to observe the dynamic response of tires. To overcome this problem, in this paper, an in-door test-rig model is designed and evaluated experimentally. This study was conducted by five methods, namely; design, simulation, production, and experimentally test. The dynamic response evaluated includes geometric change of tires and the change of camber angle. The model build consist of framework components, the sprung mass as a representation of aquarter car body and un-sprung mass which are components of the suspension system, wheels and tires. The results show that the proposed design construction is not only saved to handle all forces and moments but alsocan fulfilled functions to simulate the dynamic response of ¼ car model.